Knowledge Deployed in the Parenting Processes by Migrant Women in Chile; [Saberes Desplegados en Los Procesos de Crianza por Mujeres Migrantes en Chile] - Contreras-Salinas, S; Ramirez-Pavelic, M (Scalabriniano Center for Migratory Studies, 2023)
The article aims to describe some knowledge that migrant women in Chile reproduce in the teaching processes of their children, under a phenomenological perspective that encourages associating migration with the experience of living, together with proposing that tropes are a form to recognize knowledge, all from a study that was developed between 2016-2019, with a qualitative-narrative methodology of multiple cases. Three tropes that announce knowledge are exposed and analyzed: that children learn that things cost; know how to behave and one raises their children so that they do not feel less than anyone. The findings show a tension between subalternity and agency, in the intention of mothers to act in favor of a better living for their children. Concluding that the pedagogies of the home are a key analytical dimension of the migratory experience, because the lessons at home are based on the relationship between the structural and institutional devices and the strategic actions that migrant women deploy. © 2023, Scalabriniano Center for Migratory Studies. All rights reserved.